ANALISIS MINAT KONSUMEN TERHADAP JASA SALON ABE DI KOTA MANNA - Ogianto -; Abdul Rahman (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2014)
Ogianto, Abdul Rahman; An Analysis of consumer interest toward ABE Salon Services in Manna.This researchaimed to investigate the consumer interest toward services that is givenby ABE Salon in Mannaand also they interest toward its attributes. This research then used Accidental sampling as the data collecting method by spreading a questionnaire to 100 respondents. The results showed that overall the consumer’s interests toward ABE salon is very positive. It can be seen from the total index score acquired for 3,809528 (Sj ≥ 3). As for the main strength of ABE salonare rank as follows; First from the services attribute, second on the product attributes, third on the facilities attribute, fifth on the prices attributes and the last on the location attributes.Kata kunci : Minat, Jasa